Mobile immersion: an experiment using mobile instant messenger to support second-language learning. Issue 2 (17th February 2016) - Lai, Arthur
ABSTRACT: Immersion has been an acclaimed approach for second-language acquisition, but is not available to most students. The idea of this study was to create a mobile immersion environment on a smartphone using a mobile instant messenger, WhatsApp™. Forty-five Form-1 (7th grade) students divided into the Mobile Group and Control Group participated in a 3-month experiment in 2014. Net gain in vocabulary scores, on high-frequency English verbs, between pre-test and post-test was the measurement of learning progress. The statistics showed no significant difference between the two groups' means. However, within the Mobile Group, there was a significant correlation between an individual's chat frequency and vocabulary gain. Furthermore, chat histories of participants revealed a possible theme that the effectiveness of the mobile immersion might depend primarily on students' mentality toward the interactive learning environment, or specifically, whether students were ready to actually live the second language socially on the platform.